Impact of information and communication technologies in the teaching-learning process in rural area educational institutions - Zambrano-Cedeño, María Mercedes; Gómez-Macías, Rene Oswaldo; Sánchez-Giler, Karla Virginia; Yandun-Reyes, Jorge Javier (International research journal of management, IT and social sciences, 2023)
New technologies have become a necessary element in the teaching-learning process, being a highly supportive tool for teachers in being able to transmit knowledge to students. Currently, there is a lack of implementation of new technologies to achieve motivation objectives in students. The objective is to identify the barriers that exist between teachers and the implementation of ICT in education, seeking to promote and explore the participation of students in the educational process. The methodology used was descriptive to know the elements involved in this process, in addition to observation and bibliographic review. The result was that teachers need training on new technologies, and the economic difficulties that students and teachers present in the teaching-learning process were identified.